Overview of safety practices in foods for Salmonella prevention - Ahirrao, Vaibhav Surendra (Kansas State University, 2013)
It will be almost impossible to find a household or an informed consumer, completely oblivious to the health risks posed by foods. According to scientific estimates, 48 million cases of foodborne illness occur each year in the United States, causing 128,000 hospitalizations, 3,000 deaths, which costs $6.4-$77.7 billion in expenses by medical care and lost productivity. These illnesses pose a very big constant, perhaps growing, threat to a vast population. Salmonella is the most prevalent foodborne bacteria with more than 1.1 million cases annually in the United States. Increased international trade and distribution, rapid growth in antibiotic resistant bacteria, increase in the number of immunocompromised consumers and changes in agronomic and processing practices poses a very big challenge to monitor, contain and avoid foodborne outbreaks. This can result in contaminated food causing rapid, geographically widespread outbreak. In the wake of numerous recent foodborne illness outbreaks, this report focuses on current safety practices established by research and available to all the consumers. It studies a significant foodborne bacterium (Salmonella), its nature, significance, prevalence, mechanism of action, health risks and preventive safety measures. General food safety practices, to reduce or eliminate the risk, common to all the foodborne bacteria and specially Salmonella, include avoiding cross-contamination, thoroughly cooking foods to right lengths of time and temperature, washing fresh produce and fruits prior to consumption and storing foods at the right temperatures. Strict regulations in safe production, safe processing and consumer awareness is highly recommended. People participation is a must.
Keywords: Salmonella; Safety prevention; Salmonellosis vaibhav ahirrao; Food Science (0359); Microbiology (0410); Public Health (0573)